2013
DOI: 10.1371/journal.pone.0067768
|View full text |Cite
|
Sign up to set email alerts
|

ADAM33 Gene Polymorphisms and Mortality. A Prospective Cohort Study

Abstract: The ADAM33 gene is associated with the pathophysiology of Chronic Obstructive Pulmonary Disease (COPD) and atherosclerosis. In this study we investigated all-cause, COPD and cardiovascular mortality, in relation to single nucleotide polymorphisms (SNPs) in ADAM33 (Q_1, S_1, S_2, T_1 and T_2) that were genotyped in 1,390 subjects from the Vlagtwedde/Vlaardingen cohort. Participants were examined at entry in 1989/1990 and followed up till evaluation of the vital status on December 31st, 2008. Using Cox proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…We first found that T1, T2 and Q-1 were significantly associated with COPD, while Figarsk et al revealed that S1, S2, T2 and Q-1 were significantly associated with COPD in Vlagtwedde/Vlaardingen cohort [25]. Since no association was found between S1 and COPD in our previous study in a northeastern Chinese population [29], we did not include S1 in this study.…”
Section: Discussionmentioning
confidence: 99%
“…We first found that T1, T2 and Q-1 were significantly associated with COPD, while Figarsk et al revealed that S1, S2, T2 and Q-1 were significantly associated with COPD in Vlagtwedde/Vlaardingen cohort [25]. Since no association was found between S1 and COPD in our previous study in a northeastern Chinese population [29], we did not include S1 in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, investigators of the GRACE Genetics Study [ 26 ] evaluated 23 susceptibility loci for CAD and their association with recurrent MI or cardiac death; a variant upstream of ABO (rs579459) was significantly associated in initial and replication analyses with both endpoints in 2,099 acute coronary syndrome patients followed for a median five years. In studies of CAD and chronic obstructive pulmonary disease, ADAM33 was related to both all-cause and cardiovascular-related mortality in 1,390 subjects followed for 18 years [ 27 ]. In the MASS-II clinical trial of CAD and preserved left ventricular function, the 9p21 variant rs2383206 was associated with higher incidence of all-cause and cardiac-related mortality in 611 patients with established multi-vessel CAD [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, we are poor at predicting survival in coronary artery disease [ 38 ]; accurate estimation of survival outcomes is difficult, at best. Evidence has accumulated for the identification of genetic determinants of mortality in complex (non-Mendelian) diseases such as sudden cardiac death [ 39 , 40 ]; acute coronary syndrome [ 26 , 41 ]; cardiac-related death and all-cause mortality [ 27 , 28 ]; as well as all-cause mortality after acute coronary syndromes [ 42 ] [ 43 ]. These studies present candidate markers for events in samples with those at-risk but largely undiagnosed for CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Several genes under the linkage peak have previously been implicated in the pathogenesis of cardiovascular disease. The base to base peak at chromosome 19 encompassed FCAR and TNNT1 genes associated with coronary heart disease ( Iakoubova et al, 2006 ; Guay et al, 2016 ) and OSCAR and FPR2 genes associated with atherosclerosis plaque phenotype ( Goettsch et al, 2011 ; Petri et al, 2015 ), whereas the base to base peak at chromosome 20 encompassed ADAM33 and TRIB3 associated with extent and promotion of atherosclerosis ( Holloway et al, 2010 ; Formoso et al, 2011 ; Wang et al, 2012 ; Figarska et al, 2013 ; Prudente et al, 2015 ) and HSPA12B which is found to be enriched in atherosclerotic lesions ( Han et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%